The Role of Topical Vitamin D in Vitiligo: A Narrative Literature Review - Nopriyati; M. Akip Riyan Saputra; Izazi Hari Purwoko; Theresia L. Toruan (HM Publisher, 2022)
Vitamin D plays a role in the process of melanogenesis, namely increasing L-Dopa cells, inducing differentiation of immature melanocytes, and increasing melanocyte activity. The use of vitamin D in dermatology is in the treatment of vitiligo, psoriasis vulgaris, atopic dermatitis, verruca vulgaris, and alopecia. Vitiligo is an autoimmune disease of the skin in the form of depigmentation due to the destruction of melanocytes by T cells. The clinical manifestations of vitiligo are white macular lesions and no scale, asymptomatic, and symmetrical. Vitiligo can affect the patient's quality of life, so accurate therapy is needed. Standard therapy in vitiligo needs further research to find accurate therapy with minimal side effects. Topical vitamin D is a vitiligo therapy with minimal side effects. Several types of topical vitamin D with therapeutic effects in the field of dermatology are calcipotriol, calcitriol, tacalcitol, maxacalcitol, and hexafluoro-1,25 dihydroxyvitamin D3 with various dosages and preparations. The role of vitamin D in melanogenesis and immunomodulators as monotherapy or in combination with topical corticosteroids has been shown to be effective in the treatment of vitiligo. This literature review was on the role of topical vitamin D in the treatment of vitiligo.